2015
DOI: 10.1371/journal.pone.0134275
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Patient Adherence to Malaria Treatment: A Comparison of Results from Self-Report and a Customised Electronic Monitoring Device

Abstract: BackgroundSelf-report is the most common and feasible method for assessing patient adherence to medication, but can be prone to recall bias and social desirability bias. Most studies assessing adherence to artemisinin-based combination therapies (ACTs) have relied on self-report. In this study, we use a novel customised electronic monitoring device—termed smart blister packs—to examine the validity of self-reported adherence to artemether-lumefantrine (AL) in southern Tanzania.MethodsSmart blister packs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…27,[34][35][36] On the other hand, the sensitivity of these methods is poor 35,[37][38][39][40] ; they are heavily dependent on patient behavior, 41,42 affected by social desirability and recall biases, [43][44][45][46][47] and fail to provide information about the timing of doses, which is an essential 48 Accordingly, they are poorly correlated with direct methods such as MEMS and drug dosage in body fluids. 35,37,42,44,45,47 In particular, in a sample of 47 patients with apparently resistant hypertension, poor adherence was grossly underestimated by the Morisky Medication Adherence Scale-8 (26%) compared with drug monitoring (51%). 47 Compared with the latter, the sensitivity of Morisky Medication Adherence Scale-8 was found to be 26%, specificity 75%, positive predictive value 50%, and negative predictive value 51%.…”
Section: Methods To Evaluate Drug Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…27,[34][35][36] On the other hand, the sensitivity of these methods is poor 35,[37][38][39][40] ; they are heavily dependent on patient behavior, 41,42 affected by social desirability and recall biases, [43][44][45][46][47] and fail to provide information about the timing of doses, which is an essential 48 Accordingly, they are poorly correlated with direct methods such as MEMS and drug dosage in body fluids. 35,37,42,44,45,47 In particular, in a sample of 47 patients with apparently resistant hypertension, poor adherence was grossly underestimated by the Morisky Medication Adherence Scale-8 (26%) compared with drug monitoring (51%). 47 Compared with the latter, the sensitivity of Morisky Medication Adherence Scale-8 was found to be 26%, specificity 75%, positive predictive value 50%, and negative predictive value 51%.…”
Section: Methods To Evaluate Drug Adherencementioning
confidence: 99%
“…44,50 Witnessed drug intake combined with ambulatory BP measurement might appear as a gold standard but cannot give information about persistence. Its application requires a hospital environment and the involvement of dedicated, trained healthcare professionals.…”
Section: Methods To Evaluate Drug Adherencementioning
confidence: 99%
“…Studies on adherence to malaria diagnosis and treatment guidelines among healthcare workers (HCWs) in Tanzania are limited [12]; however, one study reported on adherence to artemisinin-based combination therapies (ACTs) that relied on self-report [13].…”
Section: Introductionmentioning
confidence: 99%
“…Calendared blister packaging, which meets the aforementioned criteria, has been associated with improved chronic medication adherence and may serve to further support ART adherence. 12,26,27 In fact, several participants in this study suggested blister packaging as a welcome alternative to current ART packaging. Given the drastic reduction in the number of pills required for HIV treatment, there is an opportunity to not only assess the cost-effectiveness of innovative ART packaging but also evaluate the acceptability of such packaging among PLWH.…”
Section: Discussionmentioning
confidence: 89%